Congenital hyperinsulinism associated with Hirschsprung’s disease—a report of an extremely rare case - Takeshi Shono; Kumiko Shono; Yoshiko Hashimoto; Shohei Taguchi; Masanori Masuda; Kastumi Muramori; Tomoaki Taguchi (Surgical Case Reports)
Abstract Background Congenital hyperinsulinism (CH) is a rare disease, characterized by severe hypoglycemia induced by inappropriate insulin secretion from pancreatic beta-cells in neonate and infant. Hirschsprung’s disease (HD) is also a rare disease in which infants show severe bowel movement disorder. We herein report an extremely rare case of combined CH and HD. Case presentation The patient was a full-term male infant who showed poor feeding, vomiting, and hypotonia with lethargy on the day of birth. He was transferred to tertiary hospital after a laboratory analysis revealed hyperinsulinemic hypoglycemia. The patient showed remarkable abdominal distension without meconium defecation. An abdominal X-ray showed marked dilatation of the large bowel. He was diagnosed with CH (nesidioblastosis) associated with suspected HD. He was initially treated with an intravenous infusion of high-dose glucose with the intermittent injection of glucagon. This was successfully followed by treatment with diazoxide and octreotide (a somatostatin analog). At 8 months of age, HD was confirmed by the acetylcholinesterase staining of a rectal mucosal biopsy specimen, and a transanal pull-through operation was performed to treat HD. At 14 months of age, subtotal pancreatectomy was performed for the treatment of focal CH located in the pancreatic body. His postoperative course over the past 12 years has been uneventful without any neurologic or bowel movement disorders. Conclusions Although it is extremely rare for CH to be associated with HD, associated HD should be considered when a patient with CH presents severe constipation.